Il giovane Heidegger e la decostruzione delle categorie aristoteliche. Vita e concetto - Moroncini, Bruno (Bollettino Filosofico, 2020)
During the 1920s, in the wake of Franz Brentano, Heidegger reinterpreted the Aristotelian categories as “categories of life”, using on the one hand the phenomenological method and on the other the contributions of the Philosophy of Life from Dilthey to Simmel. The result is a series of Vorlesungen in which Heidegger attempts both a direct reading of Aristotle’s texts, whose thesis of man as an animal with language, “life that speaks”, and a personal elaboration of the categories of life among which those of “poverty” and “ruin” stand out. The study of this Heideggerian production allows us to reconstruct the preparatory phases that culminated in the publication in 1927 of Sein und Zeit. Keywords: Aristotle, Category, Concept, Destruction, Life